A Perspective on the Role of Eco-Certification in Eliminating Illegal, Unreported and Unregulated Fishing - Longo, Catherine S.; Buckley, Leah; Good, Stephanie D.; Gorham, Taylor M.; Koerner, Lauren; Lees, Samantha; Liow, Shen Yan; Oloruntuyi, Oluyemisi; Schley, David; Rice, Jake; Currey, Rohan J. C. (Frontiers in Ecology and Evolution, 2021)
Illegal, unreported and unregulated (IUU) fishing activities threaten marine biodiversity, livelihoods, food security, and human rights across the globe. Often occurring in waters that are difficult to control, and across multi-sector, transboundary, value chains that are hard to regulate, such a complex and heterogeneous problem requires multiple strategies beyond sovereign nations’ legislation alone. Here we explore the mechanisms through which eco-certification, by fostering private-public and cross-jurisdiction cooperation, can incentivize fishers to adopt best practices in harvesting and ecosystem impacts mitigation, increase the transparency of fishery operations and accountability to suppliers. The Marine Stewardship Council (MSC) sets globally recognized standards for fisheries sustainability and supply chain assurance, based on the FAO Code of Conduct for Responsible Fisheries. Building on the MSC experience of over 400 certified fisheries representing 18% of global wild marine catch, we analyse examples and available information on the changes achieved by the seafood industry through engagement with the program, with particular focus on the elimination or reduction of illegal, unreported or unregulated fishing practices. We propose here that different, interlinked mechanisms come into play: the Standards provide best practice guidelines for improved catch documentation, monitoring, control and surveillance (MCS), and strengthening regulations. These lead to change either through (1) direct improvements required for fisheries to achieve the certificate (eg in Fishery Improvement Projects) or, (2) once certified, to maintain the certificate, or (3) as an emergent effect of the engagement process itself, requiring stakeholder cooperation and transparent information-sharing leading to a greater culture of compliance, and (4),